Unconventional (anti)ferroelectricity in van der Waals group-IV monochalcogenides - Fengrui Sui; Yilun Yu; Ju Chen; Ruijuan Qi; Rui Ge; Yufan Zheng; Beituo Liu; Rong Jin; Shijing Gong; Fangyu Yue; Junhao Chu (Nature Communications)
Abstract Fundamentally, ferroelectrics must belong to a noncentrosymmetric space group, limiting the exploration of more new ferroelectric materials. We circumvent this limitation by triggering structure distortion and inducing ferroelectricity in centrosymmetric van der Waals group-IV monochalcogenide GeSe semiconductor that features unexpected intrinsic out-of-plane antiferroelectricity. Double-type and single-type hysteresis loops from electric measurements, bonding distortion observed in in-situ atomic imaging, and perpendicular polarization uncovered by first-principles calculations, confirm the intrinsic out-of-plane antiferroelectricity and the antiferroelectric–ferroelectric transition induced by the vertical external electric-field. The hidden out-of-plane antiferroelectricity and field induced ferroelectric polarization in spatial-inversion symmetric GeSe makes it a new member of van der Waals layered semiconductors with both in-plane and out-of-plane ferroelectricity, and possibly, can be extended to all group-IV monochalcogenides and other centrosymmetric van der Waals layered materials.